Abundance and conservation status of Rosa gallica in Strzyżów Foothills (SE Poland) - Wójcik, Tomasz; Ziaja, Maria (Ecological Questions, 2022)
Rosa gallica is a rare, threatened, and legally protected species; hence, research on this species is important for identification of threats and development of protection strategies. The aim of the study was to characterise plant communities with Rosa gallica and to determine the habitat conditions, abundance, and diversity of selected population traits. The study was conducted in 2016-2020 in two localities (Bukowa, Kołaczyce) in Strzyżów Foothills. Twenty phytosociological relevés were made using the Braun-Blanquet method. The habitat conditions were assessed using Ellenberg indicator values. The following parameters were used to evaluate the diversity and quantitative relationships between the species in the analysed communities: Shannon-Wiener diversity (H՛), Evenness (J՛), and Simpson dominance (SIMP) indices. The size of the analysed populations was estimated based on the number of vegetative and generative shoots. Height was measured in 100 randomly selected shoots, and the number of flowers per generative shoot was additionally determined. Rosa gallica was part of the community with Brachypodium pinnatum in the Bukowa locality and occurred in the association Arrhenatheretum elatioris in Kołaczyce. The diversity indices had higher values ​​in Kołaczyce. The population in Bukowa covered an area of 500 m2 and comprised 911 (578 generative and 333 vegetative) shoots. From 1 to 10 flowers per shoot were noted. The population from Kołaczyce occupied a twofold smaller area and was less numerous, i.e. 465 (168 generative and 297 vegetative) shoots were recorded. It was also characterised by less abundant flowering (1-5 flowers per shoot). There were differences in the height of the generative and vegetative shoots. The parameter exhibited higher values in Bukowa ​​(55.17 and 36.95 cm, respectively) than in Kołaczyce (33.79 and 26.79 cm, respectively). All the habitat indices (except for K and R) and the biodiversity indices had higher values in Kołaczyce. The present results show that Rosa gallica occurs in a wide range of habitats varying in light, moisture, and fertility requirements. It grows in different-sized clusters or sometimes produces single shoots. Advanced succession has a negative impact on the conservation status of the population, which is particularly evident in the Kołaczyce locality. Therefore, the conservation of this species will depend on active protection measures.